Rehabilitation Protocol Variability Following Arthroscopic Bankart Repair and Remplissage for Management of Anterior Shoulder Instability: A Systematic Review - Juan B. Villarreal-Espinosa; Michael M. Reinold; Mohammad Khak; Mohammad J. Shariyate; Carol Mita; Jeffrey Kay; Arun J. Ramappa (North American Sports Medicine Institute, 2024)
# Background Augmentation of an arthroscopic Bankart repair with the remplissage (ABR) procedure has shown to confer a decrease in recurrence rates, yet, at the expense of potentially compromising shoulder motion. # Purpose/Hypothesis The purpose was to examine clinical studies that described a post-operative rehabilitation protocol after an arthroscopic Bankart repair and remplissage procedure. It was hypothesized that a review of the literature would find variability among the studies and that, among comparative studies, there would be a limited distinction from protocols for isolated Bankart repairs. # Study design Systematic Review # Materials and Methods A search was conducted using three databases (PubMed, EMBASE, and CINAHL) according to the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines. The following terms were combined while utilizing Boolean operators: (Bankart lesion OR labral tear) AND (remplissage). Studies evaluating patients after arthroscopic stabilization for unidirectional anterior glenohumeral instability with the addition of the remplissage procedure and at least 1 year follow-up were included for analysis. # Results A total of 41 studies (14 Level IV, 24 Level III, 2 Level II, and 1 Level I) were included with a total of 1,307 patients who underwent ABR. All patients had \<30% glenoid bone loss and a range of 10-50% humeral head size Hill-Sachs lesion. Type and position of immobilization were the most reported outcomes (41/41) followed by time of immobilization (40/41). Moreover, 23/41 studies described their initial post-operative shoulder range of motion restrictions, while 17/41 specified any shoulder motion allowed during this restrictive phase. Time to return to sport was also described in 37/41 of the retrieved studies. Finally, only two of the 27 comparative studies tailored their rehabilitation protocol according to the specific procedure performed, underscoring the lack of an individualized approach (i.e. same rehabilitation protocol for different procedures). # Conclusion The results of the present systematic review expose the variability among rehabilitation protocols following ABR. This variability prompts consideration of the underlying factors influencing these disparities and underscores the need for future research to elucidate optimal rehabilitation. Based on the results of this systematic review and the senior authors´ clinical experience, a rehabilitation approach similar to an isolated Bankart repair appears warranted, with additional precautions being utilized regarding internal rotation range of motion and external rotation strengthening. # Level of Evidence Level 3